EXPLORING THE USE OF MUSIC IN DERADICALIZATION - Agustanto, Pulung; Simon Runturambi, Arthur Josias; ., Puspitasari (Journal of Terrorism Studies, 2024)
This study seeks to explore music as an alternative method to enrich the variety of deradicalization programs in the framework of counterterrorism. The use of ethnic and local culture-based music is not only intended to prevent radicalism but also as an instrument of recovery therapy for terrorism prisoners in correctional institutions (Lapas). The offer of the programmatic agenda departs from the assumption that deradicalization so far still lacks a cultural approach. Moreover, the archipelago has a variety of music from various ethnicities, for example Javanese music, Sundanese music, Balinese music, Ambon music, and others that are rich in spiritual and even religious values. The lack of understanding of radical groups trapped in the flow of ideology and transnational movements must be returned to their local civilization. The tones, lyrics, metaphors and rhythms of Javanese music, for example, are interesting to study in a socio-psychological framework that can be utilized in deradicalization programs. Appropriate music therapy for the Terrorist Convict should be considered in the deradicalization program. In this context, Javanese traditional music is a hypothesis that should be experimented in correctional facilities for terrorists.